2017
DOI: 10.1111/nep.12851
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor‐β activated long non‐coding RNA ATB plays an important role in acute rejection of renal allografts and may impacts the postoperative pharmaceutical immunosuppression therapy

Abstract: In conclusion, lncRNA-ATB are strongly altered in patients with acute rejection and may serve as a novel biomarker of acute kidney rejection, identifying patients with acute rejection and predicting loss of kidney function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…TCONS_00088786 and TCONS_01496394 are TGF-β/Smad3-associated lncRNAs as they contain potential binding sites for Smad3 and silencing TCONS_00088786 inhibits renal interstitial fibrosis by targeting miR-132 (Sun et al, 2017;Zhou S.G. et al, 2018). lncRNA-ATB is highly upregulated in patients with acute renal allograft rejection and renal carcinoma and is able to promote EMT (Qi et al, 2017;Qiu et al, 2017;Zhou and Jiang, 2019). lncRNA uc.412 is able to induce mesangial cell proliferation in vitro although the underlying mechanisms are unclear .…”
Section: Diverse Role Of Tgf-β/smad Signaling In Regulation Of Non-comentioning
confidence: 99%
“…TCONS_00088786 and TCONS_01496394 are TGF-β/Smad3-associated lncRNAs as they contain potential binding sites for Smad3 and silencing TCONS_00088786 inhibits renal interstitial fibrosis by targeting miR-132 (Sun et al, 2017;Zhou S.G. et al, 2018). lncRNA-ATB is highly upregulated in patients with acute renal allograft rejection and renal carcinoma and is able to promote EMT (Qi et al, 2017;Qiu et al, 2017;Zhou and Jiang, 2019). lncRNA uc.412 is able to induce mesangial cell proliferation in vitro although the underlying mechanisms are unclear .…”
Section: Diverse Role Of Tgf-β/smad Signaling In Regulation Of Non-comentioning
confidence: 99%
“…Qiu et al [132] propose that lncRNA-ATB, activated by TGF-β1, could be used as a novel diagnostic biomarker to identify the severity of inflammation and fibrosis. Some studies investigated lncRNA-ATB, a lncRNA associated with liver fibrosis and HCC, in HCV patients and identified that plasma levels of this lncRNA were significantly correlated with the stage of liver fibrosis [133,134].…”
Section: Lncrna-atbmentioning
confidence: 99%
“…A growing body of evidence indicates that lncRNAs could regulate gene expression at the transcriptional and/or post-transcriptional levels, and play fundamental roles in a diverse array of biological processes such as cell cycle control, development, carcinogenesis, and immune response [12-15]. A large number of dysregulated lncRNAs have been identified in the renal cortex tissues of AR recipients [16-18]. Recently, Lorenzen and colleagues have analyzed the lncRNA expression profiles in the urine of renal transplant recipients, and demonstrated that urinary RP11-354P17.15-001 could serve as a novel biomarker of acute T cell-mediated rejection (ATMR) of renal allografts [19].…”
Section: Introductionmentioning
confidence: 99%